The consistent background color preference highlights the personality in the lined seahorse, Hippocampus erectus - Li, Siping; Liu, Xin; Lin, Tingting; Zhang, Dong; Zou, Xiong (Frontiers in Marine Science, 2022)
Background color in aquaculture has been paid more attention due to the effect on fish growth, survival, health, and reproduction. In the present study, we evaluated the background color preference of the lined seahorse (Hippocampus erectus) and its relationship with personality. Preference was assessed over 10 consecutive days through allowing the lined seahorse to freely choose six different colored compartments, i.e., white, red, green, black, yellow, and blue backgrounds. To minimize the spurious preference response, the individual preference index (PI) was applied to calculate the preference intensity of the background colors. Preference reliability was further verified by a binary choice test through the choice for the most preferred or non-preferred color. Preference consistency under stress situation was assessed by a “knock-at-the-door” test as confining the seahorse in a transparent circle after a 30-s air exposure and measuring the proportion of knock toward different colored backgrounds. The personality was conjointly analyzed by new environment test and novel object test. Overall, the lined seahorse showed a general preference for white and blue while avoidance of black and red backgrounds at either unstressed or stressed situations. The shyer the seahorse was, the more preference for white background it displayed. Thus, white and blue background colors are recommended for culturing the lined seahorse. Furthermore, white color preference is a potential indicator in personality study of the lined seahorse.